Trade Interconnectedness : The World with Global Value Chains. (Policy Papers; Policy Paper, 2013)
The aim of this paper is to address the implications of Global Value Chains (GVCs) for the Fund's surveillance work. The paper first draws on the World Input-Output Database (WIOD) to document the dynamics of trade linkages between countries and regions through GVCs and its impact on the real economy. The paper then examines the implications of GVCs for the real effective exchange rate (REER), a key tool used at the Fund for bilateral as well as multilateral surveillance work, and shows the potential benefit of revisiting the REER formula in light of the increasing relevance of GVCs. The paper ends with implications of GVCs for trade and trade-related policies and the multilateral trading system.